2011
DOI: 10.1210/jc.2010-2315
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Health Impairment and Socioeducational Attainment in Young Adult Patients with Congenital Hypothyroidism Diagnosed by Neonatal Screening: A Longitudinal Population-Based Cohort Study

Abstract: These findings highlight the need for careful monitoring of neurosensory functioning, weight, and long-term treatment adequacy throughout childhood and adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
1
10

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 34 publications
5
60
1
10
Order By: Relevance
“…However, such deficits appeared to be a less pronounced problem than hearing deficits in this population, with 55% of patients declaring visual problems, vs 48% of the general population (29). Visuospatial problems have also been suggested in some small series of patients (73,74).…”
Section: Neurosensory Developmentmentioning
confidence: 69%
See 4 more Smart Citations
“…However, such deficits appeared to be a less pronounced problem than hearing deficits in this population, with 55% of patients declaring visual problems, vs 48% of the general population (29). Visuospatial problems have also been suggested in some small series of patients (73,74).…”
Section: Neurosensory Developmentmentioning
confidence: 69%
“…One study investigated 12 older patients, at the age of 20 years, and suggested that auditory processing abnormalities persisted in these patients (59). In our nationwide study of 1202 young adult patients, we have recently shown that, at a median age of 23.4 years, a significantly larger proportion of the CH population than of the general population reported having hearing impairment (9.5 vs 2.5%) and that the risk of developing hearing impairment was more than three times higher in these patients than in the reference population (29,60). Hearing loss was mostly detected during childhood, at a median (23-75th percentile) age of 7.0 (3.4-19.0) years and 17% of the patients who declared hearing impairment at a median age of 23.4 years had required a hearing aid since a median age of 10 years.…”
Section: Neurosensory Developmentmentioning
confidence: 82%
See 3 more Smart Citations